2017
DOI: 10.14748/ssm.v49i1.1953
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic radical cystectomy - initial experience

Abstract: INTRODUCTION: Radical cystectomy with extended pelvic lymph node dissection is the standard treatment for muscle-invasive bladder cancer. The aim of this study is to report our initial experience of our series of 22 patients who underwent laparoscopic radical cystectomy with different urinary diversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…We had a single case of such patient, operative time was 230 minutes, 2 unit blood transfusions was made, hospital stay was 8 days and patient did not suffer from any significant postoperative complication.Anakievski et al reported that, mean operative time 300 minutes, conversion rate 0 and mean hospital stay 7 days. 27…”
Section: Discussionmentioning
confidence: 99%
“…We had a single case of such patient, operative time was 230 minutes, 2 unit blood transfusions was made, hospital stay was 8 days and patient did not suffer from any significant postoperative complication.Anakievski et al reported that, mean operative time 300 minutes, conversion rate 0 and mean hospital stay 7 days. 27…”
Section: Discussionmentioning
confidence: 99%